2016
DOI: 10.14412/2074-2711-2016-4-62-64
|View full text |Cite
|
Sign up to set email alerts
|

Role of S100 Protein in the Pathogenesis of Pain Syndromes

Abstract: По определению Международной ассоциации по изу-чению боли, «боль -это неприятное ощущение и эмоцио-нальное переживание, возникающее в связи с настоящей или потенциальной угрозой повреждения тканей или опи-сываемое в терминах такого повреждения» [1]. Данное оп-ределение не только оценивает природу и происхождение болевого стимула, но и подчеркивает в равной мере ее аф-фективные компоненты и осознанную интерпретацию.В современной неврологической практике при боли в спине (дорсалгия) на различных уровнях нередко … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Previously, it was shown that a decrease in S100A8 and S100A9 production corresponded to extravasation phase of monocytes and neutrophils [35,36]. A similar phenomenon is associated with the monocyte differentiation into tissue macrophages and dendritic cells [36][37][38]. Consequently, the monocytes circulating in the peripheral blood of ВС patients are prepared for the differentiation phase.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, it was shown that a decrease in S100A8 and S100A9 production corresponded to extravasation phase of monocytes and neutrophils [35,36]. A similar phenomenon is associated with the monocyte differentiation into tissue macrophages and dendritic cells [36][37][38]. Consequently, the monocytes circulating in the peripheral blood of ВС patients are prepared for the differentiation phase.…”
Section: Discussionmentioning
confidence: 87%